Comparative Evaluation of Thoracoscopic Pericardial Drainage and Subxiphoid Tube Insertion in Patients with Prior Cardiac Surgery - Kahraman, Doğan; Emiroğlu, Ozan (European Journal of Therapeutics, 2023)
Objective: Clinically symptomatic pericardial effusion (PE) develops in 0.8-5% of patients after open-heart surgery, and delayed effusion is related to morbidity. Comparative evaluation of the outcomes of thoracoscopic pericardial drainage and subxiphoid tube pericardiostomy, which is the standard surgical procedure, has been scantily reported. Methods: We conducted a longitudinal observation of delayed PEs treated with thoracoscopic pericardial drainage (TPD group; 48 patients) and subxiphoid pericardiostomy (SX group; 91 patients) between May 2012 and June 2017. Changes in the hemodynamic parameters, functional status of patients, and procedure outcomes were compared between the two procedures. Results: The TPD group had a significantly greater size of effusion (3.9±0.6 cm vs. 3.1±0.5 cm; p<0.01), higher pulmonary artery pressure (41.2±9.8 mmHg vs. 36.4±5.6 mmHg; p<0.01), and less time interval to emerge symptoms [6 weeks (3–15 weeks) vs. 8 weeks (3–21 weeks); p<0.01). Even though the mean operation time was shorter in the SX group (44.6±12.2 min vs. 69.2±22.3 min; p<0.01), the same amount of fluid was drained (637.9±182.9 mL vs. 661.3±168.4 mL; p=0.45). Improvements in postoperative hemodynamic variables and functional status following both procedures were similar, but symptomatic and echocardiographic recurrence of effusion was significantly more in the SX group (19 patients; 20.9% vs. 2 patients, 4.2%; p<0.01) within approximately 2 years of follow-up. Conclusion: The post-pericardiotomy effusion is a chronic inflammatory process, and the SX drainage provides temporary resolution. TPD may provide equally favorable surgical outcomes; however, it is generally performed to treat more complicated PEs.